The Basic and Middle Education Concept as A Step of Students in Planting Value Establishment since Early - Harningsih Fitri Situmorang (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
This study aims to find out, about how the importance of primary and secondary education as a way or step for students to be more independent through a work produced through entrepreneurship education, the authors believe that entrepreneurial values are very important to instill early on, because entrepreneurship is the heart of economic defense in every perspective, education is one of the many ways to make students more creative and fully independent. The research method by the author uses the systematic method Literature Review, by gathering several sources of information from journals, books and other articles. To improve the source of reading that will be produced by the reader later. Then after the sources are collected, the new author can conclude what results have been obtained from this reading source.